The Impact of Stock Introduction on Companies’ Performance: Case of Casablanca Stock Exchange - Zougarh, Mariyem; Gharnit, Said (Archives of Business Research, 2024)
This study examines the impact of the introduction to stock market on the companies’ performance in order to investigate the post-Initial Public Offering (IPOs) effects for 30 Moroccan companies listed on the Casablanca Stock Exchange (CSE). The research employs a set of 20 indicators, divided into economic, commercial, and financial indicators, to represent different aspects of companies’ performance. Based on the panel of these companies and indicators ranging on 7 years horizon, including a year before stock market introduction, we conduct the Ordinary Least Square (OLS) to examine the effect of IPO on each indicator separately. The results show that companies benefit from revenue growth and a solid asset base, which is crucial for stability. However, the efficiency in using assets to generate income and the profitability of equity are still limited and raise concerns. Moreover, and despite the level of debt being monitored, companies still seem relatively healthy from a financial structure perspective.